The Effect of Tax Incentives and Cash Flow on Accounting Conservatism (Case Study of a Food and Beverage Sub-Sector Manufacturing Company Listed on the Indonesia Stock Exchange in 2020-2022) - Olifia Tala; Rocyke Pangkey; Valencia Tumiwa (ACCOUNTABILITY, 2024)
Every company is required to be careful in preparing financial reports to avoid fraud. However, there are still many companies that are not careful in preparing their financial reports, so many cases of financial report manipulation occur. The study aims to examine the effect of tax incentives and cash flow on accounting conservatism in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The method used in this study is quantitative method. The population in this research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for 2020-2022. The purposive sampling method is a method used to determine the number of samples to be studied based on certain criteria, so that there are 20 companies that meet the criteria as needed by the author. Panel data regression analysis is used as a data analysis technique with EViews 12 software as a research tool. The research results show that (1) tax incentives have a negative and significant effect on accounting conservatism and (2) cash flow has a positive and significant effect on accounting conservatism. Keywords: Tax, Incentives, Cash Flow, Accounting, Conservatism